1987
DOI: 10.1002/art.1780300609
|View full text |Cite
|
Sign up to set email alerts
|

Myoadenylate deaminase deficiency and forearm ischemic exercise testing

Abstract: Myoadenylate deaminase (MADA) deficiency has been associated with symptoms of postexertional aches, cramps, weakness, and skeletal muscle dysfunction. Measurement of plasma lactate and ammonia concentrations after forearm ischemic exercise has been suggested as a screening test for this disorder. We performed forearm ischemic tests on 3 patients with histochemically defined MADA deficiency and 13 healthy control subjects, in a standardized fashion. Our results demonstrated that subject effort and/or performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…The forearm exercise test in MADD patients produces a normal increase of venous lactate but no rise in ammonia, hypoxanthine, or other ATP degradation products (Fig. 6.3b ) [ 66,67 ] . When enzymatic testing for myoadenylate deaminase and AMPD1 genetic mutation analyses are used as gold standards, the sensitivity of the forearm exercise test for MADD is 100 %, but the speci fi city is 37 % [ 14 ] .…”
Section: Myoadenylate Deaminase De Fi Ciencymentioning
confidence: 99%
See 1 more Smart Citation
“…The forearm exercise test in MADD patients produces a normal increase of venous lactate but no rise in ammonia, hypoxanthine, or other ATP degradation products (Fig. 6.3b ) [ 66,67 ] . When enzymatic testing for myoadenylate deaminase and AMPD1 genetic mutation analyses are used as gold standards, the sensitivity of the forearm exercise test for MADD is 100 %, but the speci fi city is 37 % [ 14 ] .…”
Section: Myoadenylate Deaminase De Fi Ciencymentioning
confidence: 99%
“…An increase in serum lactate but not ammonia has been reported in a patient with "exertional myalgia syndrome" who had normal MADD activity in a muscle biopsy specimen [ 68 ] . Measurement of hypoxanthine and other ATP degradation products (IMP and inosine) reportedly increases the speci fi city of forearm exercise test for MADD, but is not usually performed in the clinical setting [ 67,69,70 ] …”
Section: Myoadenylate Deaminase De Fi Ciencymentioning
confidence: 99%
“…The ischemic forearm exercise test allows also a presumptive diagnosis of MADD when a negligible increase in blood ammonia despite a normal rise in lactate occurs [50][51][52].…”
Section: Ischemic Forearm Exercise Testmentioning
confidence: 99%
“…Performance is de®ned as the combination of work and duration and is important, as it became clear that inadequate generation of lactate and ammonia cannot be considered pathological unless adequate effort has been documented during the test. 4 The same authors also concluded, however, that there is no need for elaborate equipment to assess exactly the amount of work performed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Valen et al 4 reported that lactate concentrations were increased from a baseline of 1´0 mmol/L (range 1´0±1´8) to 6´4 mmol/L (range 4´0±10´5).…”
mentioning
confidence: 99%